Sectoral Policies for Climate Change Mitigation in the EU - Arregui, Nicolas (Departmental Papers; Departmental Paper ;, 2020)
This paper discusses sectoral policies needed to achieve the ambitious greenhouse gas (GHG) emissions reduction targets announced in the European Union's Green Deal, complementing the companion paper 'EU Climate Mitigation Policy', which focuses on broader EU-level policies. With total emissions nearly a quarter below their 1990 level, the EU has made important progress, but the new goals will require much stronger policy action. Moreover, progress has varied across sectors. Emissions from power and industry have fallen by about a third, buildings by a quarter and agriculture by a fifth - while transport emissions have risen. This paper argues that this divergence reflects differences in effective carbon prices, but also cost differences among the available abatement channels, market imperfections, and policy gaps. It discusses specific sectoral policies needed to address these factors and achieve the new emissions reduction goals.